The Mechanisms of Alcohol Control - Christopher S. Carpenter; Carlos Dobkin; Casey Warman (Institute for the Study of Labor (IZA), 2014)
A substantial economics literature documents that tighter alcohol controls reduce alcohol related harms, but far less is known about mechanisms. We use the universe of Canadian mortality records to document that Canada's Minimum Legal Drinking Age (MLDA) significantly reduces mortality rates of young men but has much smaller effects on women. Using drinking data that are far more detailed than in prior work, we document that the MLDA substantially reduces 'extreme' drinking among men but not women. Our results suggest that alcohol control efforts targeting young adults should focus on reducing extreme drinking behavior.
Keywords: I18; 330; alcohol control; MLDA; mechanisms